Strategi Marketing Public Relations Gedung Wayang Orang Sriwedari dalam Membangun Brand Awareness Melalui Media Sosial - Fauzi Nanda Saputra; Rahmat Wisudawanto; Esfandani Peni Indreswari (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Wayang Orang Sriwedari is a traditional Javanese theater performance that adapts the stories in the puppet show which has been established since 1911. The existence of the Sriwedari Wayang Orang Building cannot be separated from the role of a public relations in creating a Marketing Public Relations Strategy. The results of the research conducted show that the public relations of the Sriwedari Wayang Orang Building uses a three-way strategy analysis consisting of pull strategy, push strategy, and pass strategy. In these three strategies, the pull strategy is the most done, which is 7 ways. While in the push strategy there are 4 ways and the pass strategy is 4 ways.The type of research used is descriptive qualitative. The data sources in this study are primary data and secondary data. The data collection techniques used are interviews, documentation, and observation. Researchers distributed questioners to find out the level of brand awareness as an achievement of the three strategies that have been carried out. Data analysis is obtained in the field with stages, namely data reduction, data presentation, and conclusion drawing. Of the three strategies that have been carried out by public relations of the Sriwedari Wayang Orang Building, the main problem is that the level of brand awareness is still at the level of unaware of the brand with the achievement of a pull strategy of 74%, push strategy 90%, and pass strategy 80%In order for the uploads made by Sriwedari Wayang Orang Building to be understood, an explanation is needed so that it can be fully understood by the reader.